Odpowiedzi

2010-04-06T17:58:16+02:00
Vk = 4/3π*4*4*4+4/3π*3*3*3+4/3π*5*5*5
Vk = 256/3π+108/3π+500/3π
Vk = (256π+500π)/3+36π
Vk = 756/3π+36π
Vk = 252π+36π
Vk = 288π

V = 4/3πR³ |:4/3π
R³ = V:4/3π
R³ = 3/4V:π
R = ∛(0,75V:π)

R = ∛(0,75*288π:π)
R = ∛216
R = 6

Pc k = 4*π*6²
Pc k = 4*π*36
Pc k = 144π [cm²]
22 3 22
2010-04-06T18:02:55+02:00
V=4/3πr³
r₁=4 cm
r₂=3 cm
r₃=5 cm


V₁=4/3π*4³
V₁=4/3π*64
V₁=256/3π

V₂=4/3π*3³
V₂=4/3π*27
V₂=108/3π

V₃=4/3π*5³
V₃=4/3π*125
V₃=500/3π

V=256/3π+108/3π+500/3π
V=864/3π
V=288π cm³

P=4πr²

288π=4/3πr³
r³=288π/π*3/4
r³=216
r=6 cm

P=4π*6²
P=144π cm²
30 4 30